PROJECT MANAGEMENT IN BUSINESS: APPLICATION IN THE CONTEXT OF INTERACTION WITH FUNCTIONAL AND PROCESSING APPROACHES - Cherchata, A. O. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2019)
In the process of economical shifting to an innovative type of development, implementation of investment and innovation projects, a considerable attention is paid to project management. Project management, like change management, is a well-developed field of management theory. Project management implies the application of certain approaches, the most common are functional and process approaches. The purpose of the article is to consider the application of project management in the context of interaction with functional and process approaches. Critical analysis of scientific views on functional and process management is carried out. It is proved that, in spite of all the advantages of the process approach, it is the functional specialization that provides the least costly execution of individual operations within the business process of the project. The result of both functional and process approaches is the simultaneous design of the organizational structure (functional areas) and the order of interaction within this structure (processes). The interaction and combination of functional and process approaches from the point of view of project management are highlighted. Due to this, a comparative analysis has been made on the criteria: orientation approaches, the interaction of structural units, the principle of constructing the organizational structure, the object of management, the concentration of management, the efficiency of the units, the information exchange, the speed of the adoption of managerial decisions. It is emphasized that in project management considerable attention is paid to effective coordination of work of separate units and strengthening of constructive interaction between functional units involved in the project. Thus, it has been proved that the synergy between functional, process and project approaches ensure manageability, efficiency in decision-making and increasing the efficiency of business processes.